Evaluation of Mental Health Services: Family Experiences, Stigmatization, Health Cadres Schizophrenia in Semarang City - Aulia, Namira; Raharjo, Bambang Budi; Widowati, Evi (Universitas Negeri Semarang, 2025)
Schizophrenia is the most common mental illness, with prevalence of 1.7 million in Indonesia. In 2020, 58.9% of patients with schizophrenia in Indonesia received services. This means that 41.1% of patients with schizophrenia, haven’t received comprehensive services. Central Java has a 9.8% prevalence of mental disorders and ranks fifth in terms of the highest number of schizophrenia patients. This will undoubtedly impact the quality of life for schizophrenia patients. The aim of this study is to evaluate mental health services, focusing on family experiences, stigmatization, and role of community health workers in schizophrenia cases in Semarang City. The research design used a qualitative descriptive phenomenological, employing in-depth interviews and purposive sampling, along with triangulation from several informants, including the experiences of families of people with mental disorders, cadres staff, and collaboration with the Social Affairs Department. Data analysis techniques used thematic analysis based on the CIPP model, using NVivo 15 software. The results showed that mental health services in Semarang had a positive impact on schizophrenia. However, there is still need to strengthen aspects of resources, cross-sector involvement, and anti-stigma strategies. Sustained collaborative interventions are needed to ensure the holistic quality of life for patients and their families.